PERSEPSI PEDAGANG DI BOJONEGORO TERHADAP KEPERCAYAAN ADANYA KLENIK SEBAGAI PENGLARIS DAGANGANNYA - Moch Suberi (Jurnal Manajemen dan Penelitian Akuntansi (JUMPA), 2014)
In economic theory there is the behavior of the producers that minimize costs include raw material costs, labor costs and overhead costs, which includes the optimization of the cost to produce goods of quality, affordable prices and maximize profits , Many traders use a variety of strategies to gain a reasonable start up does not make sense. The research method is qualitative. This type of method is qualitative field study. Object (informants) from the research is that there are traders in Bojonegoro. Purpose of this study as teaching materials on business ethics in STIE Scholar and provide a broader understanding of the practice of the occult. From this research, find merchants in Bojonegoro have occult perception as negative things that can popularize merchandise.